A MAD7‐based genome editing system for Escherichia coli. Issue 5 (16th March 2023) - Mund, Markus; Weber, Wadim; Degreif, Daniel; Schiklenk, Christoph
Abstract: A broad variety of biomolecules is industrially produced in bacteria and yeasts. These microbial expression hosts can be optimized through genetic engineering using CRISPR tools. Here, we designed and characterized such a modular genome editing system based on the Cas12a‐like RNA‐guided nuclease MAD7 in Escherichia coli . This system enables the efficient generation of single nucleotide polymorphisms (SNPs) or gene deletions and can directly be used with donor DNA from benchtop DNA assembly to increase throughput. We combined multiple edits to engineer an E. coli strain with reduced overflow metabolism and increased plasmid yield, highlighting the versatility and industrial applicability of this approach. Abstract : We present a CRISPR‐MAD7 toolkit for modular genome editing in E. coli . It enables the generation of SNPs or gene deletions and can directly be used with donor DNA from benchtop DNA assembly to increase throughput. As a proof of concept, we engineered an E. coli strain with reduced overflow metabolism and increased plasmid yield.